Efficiency optimisation signature scheme for time-critical multicast data origin authentication. (2016) - Wang, Yichuan; Ma, Jianfeng; Lu, Xiang; Lu, Di; Zhang, Liumei
A great challenge of providing authentication to time-critical multicast data is the existence of low end-to-end delay in many applications such as pay-TV and the power grid scenarios. Consequently, to balance security and efficiency is still a difficult issue. The group of secret keys reused scheme of TV-HORS still cannot meet the requirements of low time delay of computation. To describe the relationship between security and efficiency for the time-critical multicast communication scenarios, we present a Game Model of Multicast Data Origin Authentication, in this paper. By analysing our model with Shannon's information and game theory, we propose an optimised re-keying scheme, contraposing the TV-HORS scheme. The advantage of breaking the security goal is negligible, even in the lowest risk-level parameter. The experiment results show that our scheme does significantly promote the efficiency of TV-HORS scheme and is the most efficient multicast data origin authentication signature scheme.